Mostly Ghostly - Zorn, Steve; Bradley, John, 1956- (Philadelphia, Pa. : Courage Books, 1991)
Abridged versions of classic chillers by Arthur Conan Doyle, Ambrose Bierce, Edith Nesbit, Washington Irving, and others.
Keywords: Ghost stories; Children's stories; Ghosts -- Fiction; Short stories